COVID 19: The reputation of the portuguese banking system. The Banking System´s performance in face of the pandemic - Brito, Joana Santana Rebelo Monteiro e (2022)
Dissertation presented as the partial requirement for obtaining a Master's degree in Statistics and Information Management, specialization in Risk Analysis and Management